Measuring Liquidity in an Emerging Market: The Tunis Stock Exchange - Rouetbi, Emna; Mamoghli, Chokri (International Journal of Economics and Financial Issues, 2014)
In recent years, researches on microstructure have experienced considerable extensions. A major question that still has no precise answer is about measuring liquidity. Several measures were proposed in the literature in order to assess and understand this concept. This diversity of measures emanates from the main feature of liquidity which is multidimensionality. However, measuring liquidity constitutes the starting point for every research in this area. Indeed, the purpose of the present paper is to revisit the most complete measure of the intraday liquidity i.e. VNET and its main properties within an emerging market setting that is the Tunis Stock exchange. Keywords: Microstructure; liquidity; emerging markets; ACD; EGARCH. JEL Classifications: C22; C41; G10.